2021
DOI: 10.1590/0102-311x00232920
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kinesiophobia in older people with acute low back pain: longitudinal data from Back Complaints in the Elders (BACE)

Abstract: This study aimed to investigate the course of low back pain (LBP) intensity over a period of 12 months in older people with and without kinesiophobia.This was an international multicenter study. LBP intensity was examined by using the Numerical Pain Scale at baseline and over five follow-up periods. The Fear-Avoidance Beliefs Questionnaire was used to measure patients’ beliefs and fears. The study included 532 older adults (non kinesiophobic = 227; kinesiophobic = 305). The individuals had moderate pain at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…53 The overall body of literature show inconsistent results, but some studies suggest that kinesiophobia and pain catastrophizing is associated with back-related disability in older adults. 9,57,65 Other potential explanations could involve health system differences, which may influence care availability, and the potential for selection bias in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…53 The overall body of literature show inconsistent results, but some studies suggest that kinesiophobia and pain catastrophizing is associated with back-related disability in older adults. 9,57,65 Other potential explanations could involve health system differences, which may influence care availability, and the potential for selection bias in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Figure 2 shows the observed median and IQRs of RMDQ over the course of the study. Most of the improvement in back-related disability occurred from baseline (median [IQR] 9 [4][5][6][7][8][9][10][11][12][13]) to 3 months of follow-up (median [IQR] 4 [1][2][3][4][5][6][7][8][9]). The variation in disability levels was large during the 1 year of follow-up, as is evident from the wide interquartile ranges and long tails.…”
Section: Clinical Course Of Back-related Disabilitymentioning
confidence: 99%
“…Clinical nurses work with patients with kinesiophobia and that occurs more frequently among patients with orthopaedic disorders, such as low back pain and total hip replacements. Felício et al (2021) found that the incidence of kinesiophobia in patients with low back pain was 57.3%, and Alsaleem et al (2021) found that the incidence of kinesiophobia in patients with total hip replacement was as high as 62.2%. Fear is an important psychosocial factor that affects the pain experience of people, and kinesiophobia leads to changes in behaviour.…”
Section: Introductionmentioning
confidence: 99%